Obstructive sleep apnea syndrome in migraine patients with early morning headache - Watanabe, Risa; Usuda, Sho; Takizawa, Tsubasa; Sekiguchi, Koji; Yamasawa, Wakako; Shibata, Mamoru; Watanabe, Narumi; Fukunaga, Koichi; Nakahara, Jin (Japanese Journal of Headache, 2022)
In clinical practice, we sometimes experience migraine patients with early morning headaches. We investigated the characteristics and relationship between early morning headache and obstructive sleep apnea syndrome (OSAS）in eight migraine patients with morning headaches who visited Headache Clinic of Keio University Hospital. Seven of eight patients had OSAS. Six patients had mild OSAS and one patient had moderate OSAS. There was tendency of positive correlation between AHI and percentage of morning headache. There is the possibility that OSAS may exacerbate migraine, and the treatment of migraine patients with early morning headache and OSAS may be a subject of future research．